Enhancing the Moisture Resistance in Asphalt Mixtures Using Epoxy Resin - Abd-Alkhaleq, Wafaa Ahmed; Ismael, Mohammed Qadir (Engineering, Technology & Applied Science Research, 2025)
Moisture damage is a critical issue that deteriorates the asphalt pavement, diminishes the road’s longevity, and increases the likelihood of road failure. This study investigates the impact of epoxy resin, recognized for its strong adhesive properties, on the moisture resistance of asphalt mixtures by incorporating three ratios: 5%, 10%, and 15%. The Marshall, Tensile Strength Ratio (TSR), and Index of Retained Strength (IRS) tests were conducted to assess the influence of the epoxy resin on the asphalt performance. The results indicated that the Marshall characteristics, as well as the asphalt mixture’s water resistance were enhanced. A 10% epoxy resin ratio was found to be the optimum content. The Marshall stability improved by 37.86 %, the TSR by 9%, and the IRS by 6.58%, relative to the original mixture. Epoxy resin supports the environmental sustainability by increasing the pavement resilience, which reduces the maintenance and reconstruction needs, lowers the carbon emissions, minimizes waste, and encourages the efficient use of resources.